Efficacy and Safety of Diet Therapies in Children With Autism Spectrum Disorder: A Systematic Literature Review and Meta-Analysis - Yu, Yuping; Huang, Jinyue; Chen, Xiaofang; Fu, Jia; Wang, Xinhui; Pu, Linjie; Gu, Chunyu; Cai, Chunquan (Frontiers in Neurology, 2022)
Objective: Autism spectrum disorder is a neurodevelopmental disorder, with a rapid increase in incidence over the past decade. Interest in alternative therapies is growing annually, such as dietary therapies including gluten-free and/or casein-free diet, and ketogenic diet. However, there is no consensus on the efficacy and safety of dietary therapy in children with ASD up to now. This study aimed to assess the efficacy and safety of these diet interventions for children with ASD based on a meta-analysis of global data. Methods: Following the established inclusion criteria, seven databases, Cochrane Library, EMBASE, PubMed, Web of Science, VIP, Wanfang, and CNKI, were searched from the inception of the databases to August 18, 2021. The Cochrane Bias risk assessment tool was used as a quality assessment tool of the included studies. Review Manager 5.4 software was used to analyze the efficacy of the included studies, taking the core autistic symptoms and scales of ASD as therapeutic efficacy evaluations. Results: In total, 7 RCTs with 338 participants were finally obtained. All studies assessed the association between core autistic symptoms and therapeutic diet, showed statistically significant effect (standard mean difference (SMD) of -0.50, 95% confidence interval (Cl): -0.72 to -0.28), in which 5 studies reported significant reductions in stereotypical behaviors (SMD of -0.34, 95% Cl: -0.62 to -0.05), and 4 trials indicated improvement in social behaviors (SMD of -0.31, 95% Cl: -0.61 to -0.01), no correlation with the length of the interventions (both less than 6 months and greater than or equal to 6 months P<0.05). 4 studies were performed a GFCF diet and 2 experiences followed a KD diet, both of two suggested improvements of ASD symptoms (P<0.05). No statistically significant changes were observed in GFD diet, cognition, and communication subgroups (all P>0.05). Conclusion: The current findings suggest that diet therapies can significantly ameliorate core symptoms of ASD, especially reduce the stereotypical behaviors and improve the social behaviors. Although the results suggest the effectiveness of dietary therapy for ASD, limited by the small sample size of RCTs, more well-designed, high-quality clinical trials are needed to validate the above conclusions.